Change at the Helm - Haider, Syed Ali (Pakistan Journal of Ophthalmology, 2011)
Ophthalmological Society of Pakistan was founded on the 19th December 1957 at the King Edward Medical College. In its meeting on the 16th November 1968 the society resolved that it should have a publication of its own publication in the tradition of American Academy of Ophthalmology. While Raja Mumtaz was appointed as the first Editor, there was little expertise in publication of a scientific journal in Pakistan at the time. The task of publication was therefore taken up by international member, an expatriate Pakistani, living in the USA, Dr. Khalid J Awan. He carried out this task admirably well for a period of eight years from 1985 to 1993. However by 1992 the society felt strong enough to start publication from Pakistan. The task of publication was then entrusted to Prof Muhammad Lateef Ch. The first publication from Pakistan came in January 1993. He carried on with the task as Chief Editor until he took over as the President of the OSP center. For the next few years Prof Jahangir Durrani was the Chief Editor of the PJO until he abruptly immigrated to the USA. The Chief Editorship of the PJO was then returned to Prof Lateef Ch. with Dr. Tahir Mahmood, as editor, as his understudy. In the beginning of 2011 Prof Lateef